ORGANIZATIONAL COMMUNICATION MEDIA IN IMPROVING MEMBER PARTICIPATION AND CONCERN IN THE MEDAN GREEN HOUSE COMMUNITY LEARNING ACTIVITY CENTER - Nurhalima Tambunan; Rita Nofianti; Hasan Basri; Sumini Abdullah (Yayasan Multidimensi Kreatif, 2025)
This study analyzes the role of organizational commu nication media in increasing member participation and awareness at the Rumah Hijau Medan Community Learning Center (PKBM). Organizational communication media is expected to be an effective tool in establishing better relationships between PKBM managers and members, as well as increasing their awareness and involvement in various activities. The method used in this study is a qualitative approach with in-depth interviews and direct observation of PKBM members and managers at Rumah Hijau.The research results indicate that the communication media used, such as social media, bulletins, and regular meetings, have a significant influence on increasing member participation in organized programs. In addition, communication media also contribute to raising members' awareness of social and educational activities at PKBM. This study provides recommendations for maximizing the use of communication media as a strategy to strengthen the relationship between the organization and its members, as well as to encourage active participation in various activities.